FACTORS AFFECTING CUSTOMER LOYALTY WITH SATISFACTION MEDIATION AT THE KINTAN BUFFET RESTAURANT - Lego, Yenny; Nellia, Nellia (International Journal of Application on Economics and Business, 2023)
The variety of lifestyles has an impact on several business fields, including the culinary field. Sales of food and beverages grew in line with rising income or the level of public consumption. Customers are the basis of a business and become an important party in the development of the company. The purpose of this research is to find out how far customer loyalty to the Kintan Buffet restaurant in Central Park Mall Jakarta is due to the quality of service received, the perceived atmosphere of the store, and how reasonable the price to be paid is. Satisfaction is the first thing before consumers become loyal. Consumer opinion was collected by distributing questionnaires online and managed to get 200 respondents. Intake of respondents using non-probability sampling method with certain criteria or purposive sampling. The collected data is then processed using the SmartPLS 3.0 program. Convergent validity testing uses the Outer Loadings test and the AVE test. Discriminant validity testing using Fornell-Larcker and Cross Loadings analysis. Reliability testing uses Cronbach's Alpha and Composite Reliability tests. Formative indicator testing uses the Multicollinearity test and the Sign of Weight test. The results of the data analysis show that the quality of service provided by restaurants, the atmosphere of the store, in this case, the restaurant, and the fairness of the prices paid positively influence customer satisfaction and also influence customer loyalty positively and significantly. Indirectly, only the atmosphere of the restaurant does not significantly affect loyalty through customer satisfaction.